Antibiotic Utilization Patterns in Patients with Ventilator-Associated Pneumonia: A Canadian Context - Tracy Chin; Barry Kushner; Deonne Dersch-Mills; Danny J. Zuege (Canadian Journal of Infectious Diseases and Medical Microbiology)
This retrospective cohort study describes the patterns of antibiotic use for the treatment of ventilator-associated pneumonia (VAP) in the Calgary Zone of Alberta Health Services. Timing, appropriateness, and duration of antibiotics were evaluated in two hundred consecutive cases of VAP derived from 4 adult intensive care units (ICU). Antibiotic therapy was initiated in less than 24 hours from VAP diagnosis in 83% of cases. Although most patients (89%) received empiric therapy that demonstrated in vitro sensitivity to the identified pathogens, only 24% of cases were congruent with the 2008 Association of Medical Microbiology and Infectious Disease (AMMI) guidelines. Both ICU (p=0.001) and hospital (p=0.015) mortality were significantly lower and there was a trend for shorter ICU length of stay (p=0.051) in patients who received appropriate versus inappropriate initial antibiotics. There were no outcome differences related to compliance with AMMI guidelines. This exploratory study provides insight into the use of antimicrobials for the treatment of VAP in a large Canadian health region. The discordance between the assessments of appropriateness of empiric therapy based on recovered pathogens versus AMMI guidelines is notable, emphasizing the importance of using as much as possible local microbiologic and antimicrobial resistance data.